Access to cyclopentenones via copper-catalyzed 5-endo trifluoromethylcarbocyclization of ynones. Issue 17 (25th July 2022) - Le, Siya; Bai, Yihui; Qiu, Jiayan; Zhang, Zuxiao; Zheng, Hanliang; Zhu, Gangguo
Abstract : A copper-catalyzed 5- endo -selective trifluoromethylcarbocyclization of ynones is realized for the direct construction of trifluoromethylated cyclopentenones. Abstract : A Cu-catalyzed 5- endo -selective trifluoromethylcarbocyclization of ynones is developed for the concise synthesis of trifluoromethylated cyclopentenones. The pivotal roles of carbonyl groups are well illustrated by experiments and density functional theory calculations.